2011
DOI: 10.1103/physrevd.83.026002
|View full text |Cite
|
Sign up to set email alerts
|

Shear viscosity of a highly excited string and the black hole membrane paradigm

Abstract: Black hole membrane paradigm states that a certain viscous membrane seems to be sitting on a stretched horizon of a black hole from the viewpoint of a distant observer. We show that the shear viscosity of the fictitious membrane can be reproduced by a highly excited string covering the stretched horizon except for a numerical coefficient. * sasai@mappi.helsinki.fi † seyedali.zahabi@helsinki.fi

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…The analytic continuation discussed in [20] concerning N gets translated to an analytic continuation in β. The arguments in favor of 17 To be precise, the m = 0 sector has a different prefactor since we dropped the m = n = 0 sector. We do not care about this, since we will drop the m = 0 sector anyway in what follows.…”
Section: Jhep03(2014)086mentioning
confidence: 99%
See 1 more Smart Citation
“…The analytic continuation discussed in [20] concerning N gets translated to an analytic continuation in β. The arguments in favor of 17 To be precise, the m = 0 sector has a different prefactor since we dropped the m = n = 0 sector. We do not care about this, since we will drop the m = 0 sector anyway in what follows.…”
Section: Jhep03(2014)086mentioning
confidence: 99%
“…2 This picture and the related correspondence principle have been studied extensively in the past by numerous authors (see e.g. [9][10][11][12][13][14][15][16][17]). The stretched horizon is located at a string length outside the black hole horizon.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that transport coefficients in the membrane paradigm agree with those of a highly excited fundamental string at the correspondence point, up to numerical coefficients [9,10]. This can be regarded as a support for string theory as a microscopic description of the stretched horizon, in spite of a few limitations.…”
Section: Introductionmentioning
confidence: 71%
“…The tensor mode of the metric perturbationb(ω) is coupled to the tensor mode of the stress tensor T (ω) in Matrix theory. 9 According to section 3.3 and (165), the linear response of the stress tensor is…”
Section: Tensor Modementioning
confidence: 99%
See 1 more Smart Citation